Implementasi Program Merdeka Belajar Kampus Merdeka pada Mahasiswa Terbuka dan Jarak Jauh sebagai Upaya dalam Menciptakan Mahasiswa Berkarakter dan Profesional - Halimah, Siti; Zulfitria, Zulfitria (Penerbit Widina, Widina Media Utama, 2024)
This research aims to examine the implementation of the Independent Campus Learning (MBKM) program at the Open University as an effort to create students with character and professionalism. The main issue addressed in this research is how distance education can support the objectives of the MBKM program, which seeks to improve the quality of human resources through an adaptive and flexible learning outcomes-based curriculum. The research method employed is a descriptive qualitative approach, which aims to holistically understand phenomena through descriptions in the form of words and language. The novelty of this research lies in the application of the MBKM program in the context of open and distance education, an area that has not been extensively studied before. The findings of this research indicate that the Open University has successfully implemented the MBKM program through various activities, such as online short courses provided by the Indonesia Cyber Education Institute (ICE-I) and the student entrepreneurship program. These programs offer flexibility and opportunities for students to develop skills and competencies relevant to industry needs, thereby producing graduates with strong character and professionalism.ABSTRAKPenelitian ini bertujuan untuk mengkaji implementasi program Merdeka Belajar Kampus Merdeka (MBKM) di Universitas Terbuka sebagai upaya menciptakan mahasiswa yang berkarakter dan profesional. Persoalan utama dalam penelitian ini adalah bagaimana pendidikan jarak jauh dapat mendukung tujuan dari program MBKM, yang bertujuan meningkatkan kualitas sumber daya manusia melalui kurikulum berbasis capaian pembelajaran yang adaptif dan fleksibel. Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif, yang bertujuan untuk memahami fenomena secara holistik dengan deskripsi dalam bentuk kata-kata dan bahasa. Kebaruan dari penelitian ini terletak pada penerapan MBKM di konteks pendidikan terbuka dan jarak jauh yang belum banyak diteliti sebelumnya. Hasil penelitian menunjukkan bahwa Universitas Terbuka berhasil mengimplementasikan program MBKM melalui berbagai kegiatan seperti short course online yang disediakan oleh Indonesia Cyber Education Institute (ICE-I) dan program mahasiswa wirausaha. Program-program ini memberikan fleksibilitas dan kesempatan kepada mahasiswa untuk mengembangkan keterampilan dan kompetensi yang relevan dengan kebutuhan industri, sehingga mampu mencetak lulusan yang berkarakter dan profesional.